MITOCHONDRIAL DNA 4977 bp DELETION IN CHRONIC CERVICITIS AND CERVIX CANCERS - Kara, M.; Tatar, A.; Borekci, B.; Dagli, F.; Oztas, S. (Macedonian Acad Sciences Arts, 2012)
Mitochondrial DNA (mtDNA) mutations have been implied in many diseases including cancer and inflammatory diseases. The aim of this study is to investigate the relationship between the 4977 bp deletion of the mtDNA and chronic cervicitis or cervix cancer in patients. The study included a group of patients with chronic cervicitis or cervix cancer, and a control group consisting of individuals without any cervical tissue disease. A total of 72 subjects in an East Turkish population were included in the study. Of these, 35 had chronic cervicitis, 21 had cervix cancer and 16 served as the control group. Isolation of mtDNA was performed from the tissues of these patients and then mtDNA deletions were studied using polymerase chain reaction (PCR). In the cancer groups, there were 9.5% heteroplasmic and homoplasmic deletions. There were no homoplasmic deletions in the cervicitis and control groups, but the frequencies of heteroplasmic deletions were 80.0 and 31.2%, respectively. Chronic inflammation leading to increased reactive oxygen species (ROS) may be the cause of the high mtDNA 4977 bp deletion frequencies in cancer and cervicitis. The older age of the cancer patient may suggest that ageing in addition to long time exposure to ROS may lead to deletions and subsequently cancer. This is the first study to investigate the relationship of the mtDNA 4977 bp deletion to chronic cervicitis and cervix cancer.
Keywords: Mitochondrial DNA (mtDNA) mutations; Chronic cervicitis; Cervical cancer